Factors associated with the use of the subdermal implant in Peru: Analysis of a population survey, 2021 - Lázaro-Motta, Ethel Maribel (2025)
Background: The use of modern contraceptives has increased, including the subdermal implant, an effective and long-lasting method. However, the determinants predisposing users to its use are not well understood, which is essential for developing family planning strategies. Objective: To determine the factors associated with the use of the subdermal implant as a contraceptive method in women of childbearing age, according to the Demographic and Family Health Survey (ENDES) of 2021. Materials and Methods: A cross-sectional analytical study where records of reproductive-age women who participated in the 2021 ENDES were evaluated, comparing those who used the subdermal implant (cases) with those who used other methods (controls). Adjusted analysis using logistic regression was used to determine the association between variables. Results: Out of 20,496 participants, 6.87% used the subdermal implant.The probability of using the subdermal implant was more significant when the participant already had a child (p<0.001; aOR:3.55) or 2 to 3 children (p<0.001; aOR:2.97) and did not live with her partner (p<0.001; aOR:2.72). On the other hand, the probability of using the subdermal implant was lower when the participant was mainly between 40 and 49 years of age (p=0.007; aOR:0.23), had their first sexual intercourse after age 26 (p<0.001; aOR:0.51) and when the decision to use the method is made with their partner (p<0.001; aOR:0.63). Conclusion: The factors associated with the use of subdermal implant as a contraceptive method in women of childbearing age were having a partner, having children and wanting the contraceptive method.